The Story of Apolonia Tochman or the Rise of the American Myth of a New Joan of Arc - Barzycka-Paździor, Agata (Acta Poloniae Historica, 2025)
The article presents the problem of the creation of historical myths using the example of the story of Apolonia Jagiełło Tochman (c. 1825–1867), an alleged participant in the Kraków Uprising of 1846 and the Hungarian Spring of Nations, who came to America with a group of Hungarian insurgents in 1848. Faced with the difficulty of separating fact from myth in her biography, it addresses the problem of the origin of the heroic myth of Apolonia Tochman, whose name is still included in many Anglo-Saxon studies devoted to legendary and historical women warriors. Treating the myth as an unverifiable and ‘immobilised’ formulation that is supposed to say something about the world, as a category of symbolic or factual truths, it attempts to answer the question of whether Tochman’s heroic myth was a product of conscious self-creation, particular interests or social needs and what was the phenomenon of Tochman’s American popularity embraced by American presidents and compared to Joan of Arc, the semi-legendary Catalina de Erauso or the Hungarian heroines of the 1848–1849 revolution.